2020
DOI: 10.1371/journal.pone.0242985
|View full text |Cite
|
Sign up to set email alerts
|

Between-module functional connectivity of the salient ventral attention network and dorsal attention network is associated with motor inhibition

Abstract: The ability to inhibit motor response is crucial for daily activities. However, whether brain networks connecting spatially distinct brain regions can explain individual differences in motor inhibition is not known. Therefore, we took a graph-theoretic perspective to examine the relationship between the properties of topological organization in functional brain networks and motor inhibition. We analyzed data from 141 healthy adults aged 20 to 78, who underwent resting-state functional magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…The salience network, in particular, is considered to segregate unexpected but salient stimuli (e.g., top signal), as well as to modulate the switch between the internally directed cognition (DMN) and the externally directed cognition (central executive network) ( Menon and Uddin, 2010 ). It has many overlapping functions with the ventral attention network which mainly enacts in the bottom-up attentional process ( Vossel et al, 2014 ; Hsu et al, 2020 ). Converging evidence has revealed that the salience network is evolutionarily conserved across mice ( Gozzi and Schwarz, 2015 ; Grandjean et al, 2019 ; Mandino et al, 2021 ), rats ( Tsai et al, 2020 ), and humans ( Gozzi and Schwarz, 2015 ; Grandjean et al, 2019 ; Tsai et al, 2020 ; Mandino et al, 2021 ).…”
Section: Time-averaged Features Of Resting-state Functional Magnetic ...mentioning
confidence: 99%
“…The salience network, in particular, is considered to segregate unexpected but salient stimuli (e.g., top signal), as well as to modulate the switch between the internally directed cognition (DMN) and the externally directed cognition (central executive network) ( Menon and Uddin, 2010 ). It has many overlapping functions with the ventral attention network which mainly enacts in the bottom-up attentional process ( Vossel et al, 2014 ; Hsu et al, 2020 ). Converging evidence has revealed that the salience network is evolutionarily conserved across mice ( Gozzi and Schwarz, 2015 ; Grandjean et al, 2019 ; Mandino et al, 2021 ), rats ( Tsai et al, 2020 ), and humans ( Gozzi and Schwarz, 2015 ; Grandjean et al, 2019 ; Tsai et al, 2020 ; Mandino et al, 2021 ).…”
Section: Time-averaged Features Of Resting-state Functional Magnetic ...mentioning
confidence: 99%
“…We note that our cognitive network comprises a large part of what has been characterized as the “multiple-demand system” (Duncan 2010) in frontal and parietal cortex, which has been associated with diverse cognitive demands and the implementation of strategies. The DA and VA networks in particular have been implicated in motor inhibition (Hsu et al 2020) and in the re-orienting of spatial attention (Corbetta and Shulman 2002, Simpson et al 2011), both processes of which are involved in explicit strategy use during visuomotor rotation learning (de Brouwer et al (2018)).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in connectivity within and between these networks in the FF and SF groups may then reflect the deliberate reorienting of attention during task performance, which would be consistent with the finding of de Brouwer et al (2018) that explicit learners alter their gaze behavior to reflect their intended aim direction in response to a visuomotor rotation. The DA network has also been implicated in motor inhibition (Hsu et al 2020), which in the VMR task is thought to be essential for the initial suppression of a motor response to the actual target prior to implementation of a re-aiming strategy (Drummond et al 2015). The reduced connectivity in the DA network in the SS compared to the FF/SF groups might then reflect weaker engagement of this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAL x DAN inter-network connection also positively correlated with route straightness (Figure 2C, 2F). The SAL x DAN network has been shown to associate with motor inhibition 20 . Taken together, we see that the two most important networks used for predicting route straightness were associated with the ability to respond to a complex external environment, including the ability to alter pre-planned motor activities.…”
Section: Resultsmentioning
confidence: 99%